Diet quality on days without breakfast or lunch – Identifying targets to improve adolescents' diet. (1st April 2019) - Medin, A.C.; Myhre, J.B.; Diep, L.M.; Andersen, L.F.
Abstract: Dietary intake in adolescents does often not align with the recommended dietary guidelines. Excess intakes of added sugar and saturated fat, and insufficient vegetable intake are among the identified challenges, which can affect future health negatively. Identifying targets to improve dietary practices is therefore essential. The current study aimed to examine the prevalence of meal skipping and if meal skipping days had a different diet quality than other days, using data from a recent Norwegian dietary survey in adolescents (n = 689, age 12–14 years). Their dietary intake was recorded for four days, using a web-based record system. Differences between days with, and without, breakfast or lunch were explored using mixed effect models, adjusting for correlated data and covariates, including weekday-weekend effect. In total, 8% and 11% were days without breakfast and lunch, respectively. Days with breakfast or lunch were associated with higher intake of fibre, and higher odds of consuming fruits and berries, juice and smoothie, than days without breakfast or lunch. Weekdays with lunch were also associated with lower intakes of added sugar and total fat (in % of energy), and discretionary foods, compared to weekdays without lunch. Skipping breakfast and lunch was associated with reduced diet quality in adolescents. Targeting these meals, and in particular school lunch, is a potential way forward to improve adolescents' dietary intake.